2021
DOI: 10.1093/abbs/gmab009
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of ProBeptigen/CMI-168 on aging-induced cognitive decline and neuroinflammation in mice: a comparison with essence of chicken

Abstract: Neuroinflammation and cognitive decline are the key pathological features in aging that bring detrimental impacts upon quality of life. However, there is no effective anti-aging pharmacological therapy thus far. Dietary supplements in particular essence of chicken (EC) has been found to be an effective remedy for alleviating mental stress and improving memory. In addition, a novel hydrolyzed chicken extract, ProBeptigen/CMI-168 (PB), showed beneficial effects on cognitive ability. However, the antiaging effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(44 citation statements)
references
References 39 publications
4
40
0
Order By: Relevance
“…A novel extract from chicken meat, that is, hydrolyzed chicken extract (HCE) has undergone a proprietary bioprocessing technology and aqueous extraction as described previously. HCE supplementation exhibited favorable neuroprotective effects in rodent studies, including improving learning ability, attenuating memory loss, and brain oxidative stress. , One recent clinical study found that HCE treatment improved stress-induced cognitive decline and alleviated inflammation in healthy middle-aged humans . In addition, our previous study suggested that HCE exerted impacts on ameliorating neuroinflammation, gliosis, oxidative stress, and cognitive decline in naturally aged mice compared with the traditional essence of chicken supplementation . However, the actual bioactive components (BCs) that contribute to the amelioration of neuropathology remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A novel extract from chicken meat, that is, hydrolyzed chicken extract (HCE) has undergone a proprietary bioprocessing technology and aqueous extraction as described previously. HCE supplementation exhibited favorable neuroprotective effects in rodent studies, including improving learning ability, attenuating memory loss, and brain oxidative stress. , One recent clinical study found that HCE treatment improved stress-induced cognitive decline and alleviated inflammation in healthy middle-aged humans . In addition, our previous study suggested that HCE exerted impacts on ameliorating neuroinflammation, gliosis, oxidative stress, and cognitive decline in naturally aged mice compared with the traditional essence of chicken supplementation . However, the actual bioactive components (BCs) that contribute to the amelioration of neuropathology remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These results imply a potential anti-aging effect of ProBeptigen ® in alleviating cognitive deficits and promoting the antioxidant defense system [32]. In the most recent study using naturally aged mice, ProBeptigen ® ameliorated age-induced cognitive decline, reduced oxidative stress, and reduced neuroinflammation in the hippocampus and cortex [34]. A pilot clinical study [33] on 20 healthy subjects with six weeks of ProBeptigen ® (670 mg/day) consumption showed that ProBeptigen ® enhanced cognitive performances on Digit Span backwards, Letter-Number Sequencing, and the Rey Auditory Verbal Learning Test (RAVLT), in terms of working memory and episodic memory functions.…”
Section: Introductionmentioning
confidence: 84%
“…The declining levels of hs-CRP, an indicator of inflammation and cardiovascular risks, during and after ProBeptigen ® treatment is noteworthy. Chronic low-grade inflammation is a hallmark of aging, and a recent study [34] in naturally aged mice showed similarly that ProBeptigen ® exerted anti-neuroinflammatory effects and significantly diminished levels of pro-inflammatory cytokines, tumor necrosis factor alpha (TNF-α), and interleukin-1 beta (IL-1β), in the hippocampus and cortex, alongside antioxidant effects and improved learning and memory. It is suggested that the reduced levels of these cytokines could be explained by significantly decreased phosphorylation levels of nuclear factor-kB (NF-kB) p65 which may contribute to many age-related neuroinflammatory diseases if immunoreactivity is enhanced for NF-kB signaling [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of recent clinical studies found that hydrolysed chicken extract treatment improved stress-induced cognitive decline and alleviated inflammation in healthy middle-aged humans [51]. Another available study by Ni et al [52] suggested that chicken meat extract ameliorated neuroinflammation, gliosis, oxidative stress and cognitive decline in naturally aged mice. Rezzani et al [2], in turn, demonstrated that a carnosine analogue improved oxidative stress, inflammation and cell metabolism, thereby becoming a greatly promising therapeutic molecule.…”
Section: Discussionmentioning
confidence: 99%